2006
DOI: 10.1200/jco.2005.02.1717
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Therapy With Growth Factor Support for Patients With Ewing Tumor Metastatic at Diagnosis: Pediatric Oncology Group/Children's Cancer Group Phase II Study 9457—A Report From the Children's Oncology Group

Abstract: Topotecan had limited activity in patients with Ewing sarcoma or PNET metastatic at diagnosis. The topotecan-cyclophosphamide combination was active. Amifostine was not myeloprotective. Overall results showed no improvement compared with previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(92 citation statements)
references
References 17 publications
6
85
0
1
Order By: Relevance
“…), whereas all recurrences were fatal by 5 years in nonimmunotherapy recipients (28.6% OS vs. 28.6% PFS at 5 years.). Together, the data demonstrate favorable OS in participants who initiated immunotherapy on this trial compared with outcomes previously been reported in this population, raising the prospect that immunotherapy provided benefit (6)(7)(8)(9)(10)(11)(12)(13)17).…”
Section: Clinical Outcomesmentioning
confidence: 53%
See 1 more Smart Citation
“…), whereas all recurrences were fatal by 5 years in nonimmunotherapy recipients (28.6% OS vs. 28.6% PFS at 5 years.). Together, the data demonstrate favorable OS in participants who initiated immunotherapy on this trial compared with outcomes previously been reported in this population, raising the prospect that immunotherapy provided benefit (6)(7)(8)(9)(10)(11)(12)(13)17).…”
Section: Clinical Outcomesmentioning
confidence: 53%
“…1-3) and rhabdomyosarcoma (RMS; ref. 4,5), but patients presenting with metastatic disease experience dismal survival, despite high response rates (6)(7)(8)(9)(10)(11)(12). Survival also remains poor for patients with recurrent pediatric sarcomas (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…59,62 Non-ifosfamidebased chemotherapy regimens have also demonstrated activity and good tolerability in patients with relapsed or refractory bone sarcomas. Regimens that appear to be active in this patient group include docetaxel and gemcitabine 63 ; topoisomerase I inhibitors (topotecan, irinotecan) with cyclophosphamide and temozolomide [64][65][66][67][68][69][70] ; cyclophosphamide and topotecan 65 ; irinotecan and temozolomide 68 ; and vincristine, irinotecan, and temozolomide. 71 A review of 107 patients with relapsed or refractory Ewing sarcoma examined the combination of etoposide with a platinum agent (ie, cisplatin or carboplatin), suggesting that further study of etoposide/carboplatin may be warranted.…”
Section: Treating Relapsed/refractory Diseasementioning
confidence: 99%
“…Primary multifocal Ewing's sarcoma has been associated with an unfavorable prognosis, as evidenced by a 2-year event-free survival of 15% to 31% [3,19,26]. When compared to other patients with advanced Ewing's tumors (ie, those relapsing within 2 years of chemotherapy or suffering multiple relapses), patients with primary multifocal disease treated with contemporary chemotherapy and myeloablative therapy showed a trend toward lower rates of event-free survival at 5 years (0% to 25% versus 24% to 28% for all advanced Ewing's tumors) [5-8, 20, 24, 26].…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…Overall, the results for myeloablative therapy with melphalan have been equivocal in patients with primary multifocal disease [17,23,24]. Other therapeutic approaches under investigation include growth factor support, interleukin therapy, and immunotherapy with tumor-specific dendritic cells cultured from CD34+ progenitors [1,3,23].…”
Section: Discussion and Treatmentmentioning
confidence: 99%